Thiamine Alleviates High-Concentrate-Diet-Induced Oxidative Stress, Apoptosis, and Protects the Rumen Epithelial Barrier Function in Goats - Ma, Yi; Zhang, Ying; Elmhadi, Mawda; Zhang, Hao; Wang, Hongrong (Frontiers in Veterinary Science, 2021)
High concentrate diets are continually used in ruminants, which can lead to the occurrence of subacute rumen acidosis for ruminants. Objectives: This study investigated the effects of dietary thiamine supplementation on the damage of ruminal epithelium barrier function in goats fed a high-concentrate diet. Twenty-four healthy Boer goats (live weight of 35.62 ± 2.4 kg, aged 1 year) were randomly assigned into 3 treatments with 8 goats in each treatment consuming one of three diets: a low-concentrate diet (CON; concentrate: forage 30:70), a high-concentrate diet (HC; concentrate: forage 70:30), or a high-concentrate diet with 200 mg of thiamine/kg of DMI (HCT; concentrate: forage 70:30) for 12 weeks. Compared with HC treatment, the HCT treatment had a markedly higher GSH, SOD, GSH-PX and T-AOC (P < 0.05) in plasm and rumen epithelium. The results show that apoptosis index was lower (P < 0.05) in HCT treatment than that of the HC treatment. Compared with the HC treatment, permeability and electrophysiology parameter Isc for ruminal epithelial tissue were decreased (P < 0.05) in HCT treatment. The immunohistochemical results showed that expression distribution of TJ (Tight junction) protein including claudin-1, claudin-4, occludin, and ZO-1 was greater (P < 0.05) in the HCT treatments than that in the HC treatment. The mRNA expression of ZO-1, Occludin, Claudin-1, Bcl-2, Nrf2, SOD2, GPX1, NQO1 and HO-1 in high concentrate diet with thiamine treatment significantly increased in comparison with HC diet treatment (P < 0.05), and the mRNA expression of Caspase 3, Caspase 8, Caspase 9, Bax, LBP, TLR-4, NFκB, TNF-α, IL-1β, IL-6, TRAF-6 and had a significant decreased in HCT treatment in comparison with HC diet treatment (P < 0.05). Compared with the HC treatment, the HCT diet significantly increased the protein expression of ZO-1, Occludin, Claudin-1, NQO1, HO-1, SOD2, Akt, p-Akt, Nrf2 and p-Nrf2, conversely the expression of NFκB related protein-p65 and pp65 was significantly decreased (P < 0.05). The results show that dietary thiamine supplementation improves the rumen epithelial barrier function by regulating Nrf2 - NFκB signaling pathways during high concentrate diet feeding.